Acute toxicity of graphene nanoplatelets on biological wastewater treatment process. Issue 1 (23rd December 2016) - Nguyen, Hang N.; Castro-Wallace, Sarah L.; Rodrigues, Debora F.
Abstract : This study investigates the acute toxicity of graphene to sludge microbial communities. Abstract : This study investigates the acute toxicity of graphene to sludge microbial communities. The acute toxicity was investigated with concentrations varying from low to relatively high concentrations of graphene (between 0 and 300 mg L −1 ) to understand the impact of different concentrations of graphene on the biological wastewater treatment process. The experiments were performed with a 10 h continuous aeration using batch reactors to simulate the wastewater biological treatment process. Results showed that increasing concentrations of graphene in the reactors led to decreasing COD, BOD5, ammonia and phosphate removals. In addition, abundances of ammonia oxidizing bacteria, ammonia monooxygenase and phosphate accumulating bacteria decreased along with the overall sludge microbial metabolic activity. The 16S rRNA deep sequencing of the sludge microbial community exposed to different concentrations of graphene showed that the abundances of the two most abundant phyla, i.e. Proteobacteria and Bacteriodetes, changed with increasing concentrations of graphene. The results also showed that releases of graphene concentrations at 10 mg L −1 and higher seem to present a short term impact in the wastewater treatment process.